Mycobacteriophages in diagnosis and alternative treatment of mycobacterial infections - Ouyang, Xudong; Li, Xiaotian; Song, Jinmiao; Wang, Hui; Wang, Shuxian; Fang, Ren; Li, Zhaoli; Song, Ningning (Frontiers in Microbiology, 2023)
Antimicrobial resistance is an increasing threat to human populations. The emergence of multidrug-resistant “superbugs” in mycobacterial infections has further complicated the processes of curing patients, thereby resulting in high morbidity and mortality. Early diagnosis and alternative treatment are important for improving the success and cure rates associated with mycobacterial infections and the use of mycobacteriophages is a potentially good option. Since each bacteriophage has its own host range, mycobacteriophages have the capacity to detect specific mycobacterial isolates. The bacteriolysis properties of mycobacteriophages make them more attractive when it comes to treating infectious diseases. In fact, they have been clinically applied in Eastern Europe for several decades. Therefore, mycobacteriophages can also treat mycobacteria infections. This review explores the potential clinical applications of mycobacteriophages, including phage-based diagnosis and phage therapy in mycobacterial infections. Furthermore, this review summarizes the current difficulties in phage therapy, providing insights into new treatment strategies against drug-resistant mycobacteria.